A human rights foundation for ethical mental health practice. (21st November 2016) - Devitt, P.; Kelly, B. D.
Abstract : There are close links between clinical ethics, human rights and the lived experience of mental illness and mental health care. Principles of professional ethics, national mental health legislation and international human rights conventions all address these themes in various ways. Even so, there are substantial deviations from acceptable standards at certain times, resulting in significant violations of rights in the developing and developed worlds. An explicitly human rights-based approach has improved matters in, for example, Scotland. External drivers of change, such as legislation, standards, codes of practice, inspections and sanctions for violations, are all needed. Attitudes and culture are also critical drivers of change. Most importantly, the principles and values of ethical, human rights-based professional practice need be taught and modelled throughout professional careers. Ongoing training in this area should form a central element of programmes of continuing professional development, delivered by people with expertise and understanding, including service users.